Neutrophil gene expression in COVID-19 patients with acute respiratory distress syndrome - Ito, Hiroshi; Ishikawa, Masakazu; Yoshimura, Jumpei; Liu, Yuchen; Sakakibara, Shuhei; Sugihara, Fuminori; Matsumoto, Hisatake; Hirata, Haruhiko; Ogura, Hiroshi; Oda, Jun; Okuzaki, Daisuke (Frontiers in Immunology, 2025)
BackgroundAlthough an increase in neutrophil count has been observed in patients with coronavirus disease 2019 (COVID-19), the relationship between the systemic neutrophil transcriptome and clinical course of COVID-19 remains unclear. Hence, we examined the relationship between the clinical course and RNA sequencing analysis results in COVID-19 patients.MethodsPeripheral blood samples were obtained from 28 patients with COVID-19-associated ARDS and 16 healthy controls. Bulk RNA sequencing was performed, and clustering analysis was used to explore relationships between gene expression and clinical characteristics. In a separate cohort, neutrophils were isolated from the peripheral blood of five COVID-19 patients with ARDS for single-cell RNA sequencing to further characterize the neutrophil subpopulations.ResultsIn bulk RNA sequencing analysis, COVID-19 patients with ARDS had elevated gene expression associated with neutrophils compared with healthy controls.Clustering analysis revealed no differences in the clinical characteristics of COVID-19 patients with ARDS. In the single-cell RNA sequencing analysis, clustering analysis showed that the patients were divided into two groups: those who could be weaned from the ventilator within 28 days and those who could not be weaned.ConclusionThese findings indicate that differences in neutrophil gene expression may have important clinical implications. This study may support the exploratory identification of genomic factors, such as neutrophil gene expression, that are relevant to clinical parameters.